A Five-Level Switched-Capacitor Based Transformerless Inverter With Boosting Capability for Grid-Tied PV Applications - Sudipto Mondal (16904520) (2023)
Transformerless grid-connected inverters have attained a lot of research interest in renewable energy interface applications, due to certain promising properties like greater efficiency, light weight, affordable price, and tolerable power density. Among various types of transformerless grid-tied photovoltaic (PV) inverters, multilevel inverters (MLIs) are mostly popular due to their ability to transmit reactive power, small filter size for reducing total harmonic distortion (THD) and their common-ground (CG) configuration to mitigate the detrimental leakage current due to the parasitic capacitances of the PV array. Again, among different types of MLIs for PV systems, switched-capacitor (SC) based multilevel inverter topologies are the burning topic in current decades due to their single source requirements for producing multilevel output voltage. However, for mostly used single-phase five-level inverters, most of the existing SC based topology requires at least two SCs for power conversion. In this paper, a five-level transformerless inverter based on a single SC is proposed, requiring only seven switches, no diode, a single capacitor, and one dc voltage source. The proposed transformerless MLI also has auto-boosting capability. Notably, the number of power switches operating at high frequency is limited to three, which lowers down the switching losses of the inverter. Rather than a new single SC based five-level transformerless inverter topology, a control scheme is also presented to inject a precisely regulated current into the grid that can govern both the active and reactive power support modes. In-depth comparisons between the proposed and cutting-edge MLIs are also provided. All these claims are validated through MATLAB/Simulink and PLECS computer simulation environments. A laboratory-scaled prototype is also built and tested to support the simulated claims further and validate the effectiveness and feasibility of the proposed five-level transformerless inverter topology. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3241927